ANALYSIS OF THE SPEAKING MATERIALS IN TEXTBOOK“MANDIRI：PRACTISE YOUR ENGLISH COMPETENCE (FOR SMK AND MAK XI)”BASED ON 2006 ENGLISH STANDARD OF CONTENT (SI) (RETAIN, 2013)
BahasaInggrismemegangperananpentingdalamaspekpendidikan di sebagianbesarnegara-negara di dunia, termasuk Indonesia.Di Indonesia sendiriBahasaInggrisdiajarkandaritingkatSekolahDasar (SD) sampaidengantingkatUniversitas.MelaluiBahasaInggris, siswadiharapkanmemilikiketerampilanberkomunikasibaiksecaralisanmaupuntulis. Untukmencapaitujuanini, DepartemenPendidikanNasional Indonesia telahmengembangkan Standard KompetensibahasaInggris yang tertuang di dalamkurikulumsebagai standard proses pembelajaranbahasaInggris. Sehubungandengankurikulum, kurikulum yang sekarangditerapkan di semuajenjangpendidikan di Indonesia adalahKurikulum 2006.Masihberhubungandengankurikulum, materipembelajaran yang sebagianbesarberupabukuteksjugaharussesuaidengankurikulum.Selainsesuaidengankurikulum, bukuteksjugaharusmenyajikanempatmateriketerampilanberbahasa, yaitumateriuntukketerampilanmenyimak, berbicara, membacadanmenulis.Olehkarenaitu, penelitianinidifokuskanpadaanalisismateriketerampilanberbicaradalambukuteksberjudul "Mandiri: Practise Your English Competence (for SMK and MAK XI) yang diterbitkanolehErlangga. Penelitianinidimaksudkanuntuk (1) menganalisisrelevansimateriketerampilanberbicaradalambukuteksberjudul "Mandiri: Practise Your English Competence" denganStandar Isi (SI) bahasaInggris 2006 dan (2) untukmenganalisisrelevansimateriketerampilanberbicaradalambukuteksberjudul "Mandiri: Practise Your English Competence" dengankriteriamateriketerampilanberbicara yang baik yang diadaptasidarievaluasibukuteksbahasaInggrisuntuk SMK dari BSNP. RancanganpenelitianiniadalahdeskriptifkualitatifdanobyekpenelitianiniadalahbukuteksbahasaInggrisberjudul: "Mandiri: Practise Your English Competence )". Hasilpenelitianinimenunjukkanbahwa (1) materiketerampilanberbicaradalambukutersebutcukuprelevandenganmateriketerampilanberbicara yang adadalamStandar Isi (SI) bahasaInggris 2006 dan (2) jugacukuprelevandengankriteriamateriketerampilanberbicara yang baik yang diadaptasidari BSNP. Selainitu, materiketerampilanberbicara yang ada di dalambukuiniperludirevisisehinggatujuanpengajaranbahasa, khususnyapengajaranmateriketerampilanberbicaradapatdicapai. Kata Kunci:analisis, materiketerampilanberbicara, bukubahasaInggris, Standar Isi (SI) bahasaInggris 2006, BSNP. Abstract English plays special role in education aspect in most of the countries in the world, one of them is Indonesia. In Indonesia English is taught from elementary school to university level. Through English, the students are expected to have good communication skill either in spoken or written form. To achieve this aim, the National Education Department of Indonesia has developed an English standard competence which is stated in curriculum as the standard of English and learning process. Related to curriculum, the present curriculum which is used in all level of education in Indonesia is 2006 Curriculum. Related to curriculum, learning materials which are mostly in the form of textbook should be based on the curriculum. Besides in line with the curriculum, the textbook should provide materials covering four language skills, they are: Listening, Speaking, Reading and Writing materials. Therefore, this study focused on the analysis of speaking materials in the textbook entitled “Mandiri: Practise Your English Competence for (SMK and MAK XI) published by Erlangga. This study was intended (1) to analyze the relevance of the speaking materials in textbook “Mandiri: Practise Your English Compentence” to the 2006 English standard of content (SI) and (2) to analyze the relevance of the speaking materials in textbook “Mandiri: Practise Your English Compentence” to the criteria of good speaking materials adapted from English textbook evaluation for vocational high school of BSNP. The design of this study was descriptive qualitative and the object of this study was the English textbook entitled: “Mandiri: Practise Your English Competence”. The results of this study shows that speaking materials in the textbook are quite relevant to the speaking materials based on the 2006 English standard of content (SI) and the speaking materials in the form of speaking exercises in the textbook are quite relevant to the criteria of good speaking materials adapted from BSNP. Furthermore, the speaking materials of this textbook need to be revised so that, the objective of language teaching, especially speaking can be reached Keywords: analysis, speaking materials, English textbook, 2006 English standard of content (SI), BSNP.